Body in the wardrobe - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery, 2016)
Attorney Sophie Maxwell has come to Savannah to be with her new husband, Will. But nothing throws cold water on a hot relationship faster than a dead body. Worse for Sophie, no one believes the body she knows she saw is real. Fortunately, Sophie has a good friend in Faith Fairchild. With teenage Amy being bullied by mean girls and husband Tom contemplating a major life change that will affect all the Fairchilds, Faith is eager for distraction in the form of some sleuthing. In between discussions of newlywed agita, surprising Savannah customs and, of course, fabulous low country food, Faith and Sophie will pair up to unmask a killer!